Vocabulary Acquisition in a Foreign Language: Digital Technologies and Learning - Costa, Larissa T. da; Silva, Carolina Morais R. da (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2021)
The advancement of Information and Communication Technologies (ICTs) over the last decades has resulted in the integration of technology into most of our daily tasks, especially in education. Foreign language learners now have access to a plethora of tools available on mobile devices, including audiovisual tools that support their pronunciation enhancement and vocabulary acquisition process. Considering the benefits of using technology in the classroom, this paper demonstrates a video-recording method used in favor of autonomous foreign language learning.